Closed‐form expression to optimize the fiber Bragg grating sensor apodization performance. Issue 8 (August 2017) - Chaoui, Fahd; Aghzout, Otman; Alejos, Ana Vazquez; Falcone, Francisco; Naghar, Azzeddin; El Yakhloufi, Mounir
Abstract: In this article, a new closed‐form apodization expression, which describes the light propagation in fiber Bragg grating sensor (FBGS) according to the design setting of the sensor application, is developed and presented. The main goal of the proposed approach is to optimize the FBGS apodization to enhance the reflected power as long as side lobes are kept in a low level. For this purpose, the coupled mode equations (CME) method has been used with the new apodization formula to customize the light propagation in the FBGS. The new apodization algorithm is processed based on side lobe level (SLL) and full width at half maximum (FWHM) of the FBGS grating spectrum. Further, the developed method has been compared with other apodization profiles presented by other authors. All results show very satisfactory performance of the proposed method.